2015
DOI: 10.1111/jcpe.12463
|View full text |Cite
|
Sign up to set email alerts
|

Oral microbiome in chinese patients with aggressive periodontitis and their family members

Abstract: There is a kinship in the phylogenetic architecture of microbiota among Chinese AgP patients and their family members. P. gingivalis might be a predominant pathogen in these Chinese AgP patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
38
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 64 publications
6
38
1
Order By: Relevance
“…Aside from the age on onset, the location of the lesions, and the rapidity of the breakdown, there are several added features that appear to be unique to LAgP. For example it has been reported that; 1) PMNs and macrophages show a level of hyperactivity, 2) antibody responsiveness can be elevated either at a peripheral or local level, 3) specific subpopulations of bacteria are prevalent in specific populations and 4) a particularly thin biofilm composed of Gram negative bacteria have been reported on root surfaces of LAgP subjects …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aside from the age on onset, the location of the lesions, and the rapidity of the breakdown, there are several added features that appear to be unique to LAgP. For example it has been reported that; 1) PMNs and macrophages show a level of hyperactivity, 2) antibody responsiveness can be elevated either at a peripheral or local level, 3) specific subpopulations of bacteria are prevalent in specific populations and 4) a particularly thin biofilm composed of Gram negative bacteria have been reported on root surfaces of LAgP subjects …”
Section: Discussionmentioning
confidence: 99%
“…Studies from 1998 forward examined a broad spectrum of bacteria using DNA technologies ( Table 2). [23][24][25][26][27][28][29][30][31][32][33][34][35][36] In one-half the studies Aggregatibacter actinomycetemcomitans was implicated as a risk marker, and in another half Porphyromonas gingivalis, 23,25,27,[32][33][34][35] Tannerella forsythia, 27,29,32,34,35 and Selenomonads emerged as markers of risk (Table 2). A recent study 37 showed that in younger individuals A. actinomycetemcomitans was associated with disease whereas this was not the case in older subjects.…”
Section: Relevant Findingsmentioning
confidence: 99%
“…Comparing results of NSPT on subjects with GAgP with results on a cohort in subjects with CP (Jiao et al., ), the improvement after treatment in patients with GAgP may be even better than that of CP: Firstly, mean PD reduction at site level of GAgP patients for all sites was greater than that of CP patients (1.17 mm versus 0.65 mm); Secondly, multilevel analysis, which adjusted many influential factors of NSPT also showed that interceptions of the models in patients with GAgP, both for all sites and baseline deep sites, were greater than that of CP patients. Better response to NSPT of patient with GAgP may be attributed to the genetic (Deng et al., ; Li et al., ) and/or microbial diversity (Han et al., ; Li, Feng, et al., ; Li, Xu, et al., ) of the two diseases and better wound healing in patients with GAgP whose mean age was younger than that of CP.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, oral hygiene of Chinese patients is worse and their awareness of periodontal diseases is less sufficient, in general, than subjects from developed countries. This fact might result from that treatments for subjects with GAgP were initiated at more advanced stage of the disease and ethnic difference in genetics, e.g., genotype frequencies of polymorphisms vitamin D receptor gene (Deng et al, 2011), and microbiology, e.g., the presence of Aggregatibacter actinomycetemcomitans between Chinese and Caucasians (Han et al, 1991;Ishikawa, Kawashima, Oda, Iwata, & Arakawa, 2002;Kononen & Muller, 2014;Li, Feng, et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation